Cost-effectiveness of PD-L1 testing to guide immunotherapy for patients with non-small cell lung cancer in China - LI Yuan, GUO Lingchuan, YUAN Yong, ZHENG Qiang, JIN Yan, MING Jian (Zhongguo aizheng zazhi)
Background and purpose: According to the latest data from the National Cancer Center, the incidence rate and mortality of lung cancer in China rank first among all malignant tumors, and 85% are non-small cell lung cancer (NSCLC). In recent years, immunotherapy based on programmed cell death protein-1 (PD-1)/programmed death ligand-1 (PD-L1) immune checkpoint inhibitors (ICIs) has made breakthrough progress in lung cancer, bringing more survival benefits to lung cancer patients. This study aimed to evaluate the cost-effectiveness of three major PD-L1 testing assays in guiding immunotherapy for patients with NSCLC, and to provide empirical evidence to guide the selection of cost-effective diagnosis and ICIs monotherapy regimens for NSCLC patients in China. Methods: From a healthcare system perspective, a decision-tree model was constructed to simulate the cost and effectiveness (percentage of the patients who were successfully diagnosed and who were correctly prescribed and underwent correct treatment according to China treatment guidelines) of employing Ventana PD-L1 IHC (SP263) assay, PD-L1 IHC 22C3 pharmDx, and Dako 22C3 antibody concentrate in early to mid-stage and advanced NSCLC patients in China, respectively. The cost-effectiveness of SP263 assay compared to other testing methods was assessed through the incremental analysis. The robustness of the base case analysis results was validated by using one-way sensitivity analysis and probabilistic sensitivity analysis. Results: When considering atezolizumab monotherapy following chemotherapy for early to mid-stage (Ⅱ A-Ⅲ B) NSCLC patients, in comparison to the 22C3 assay or 22C3 antibody concentrate, the SP263 assay incurred an additional cost of 9 449 yuan per successfully diagnosed and treated patient. The SP263 assay, which can guide multiple ICIs monotherapies (e.g., atezolizumab, pembrolizumab) for advanced (Ⅳ) NSCLC patients, was dominant by achieving a higher percentage of successfully diagnosed and treated patients at a lower cost compared to Dako 22C3 assay and Dako 22C3 antibody concentrate. One-way sensitivity analysis and probabilistic sensitivity analysis both confirmed the robustness of the results. Conclusion: The Ventana PD-L1 IHC SP263 assay was cost-effective, compared to Dako PD-L1 IHC 22C3 assay and Dako 22C3 antibody concentrate for the immunotherapy treatment for both stage Ⅱ A-Ⅲ B and stage Ⅳ NSCLC patients in China.